Fostering Adolescents’ Self-Disclosure Through Johari Window-Based Counselling: Toward a Pedagogical Framework for Islamic Education - Fakhri Yacob; Andriansyah Andriansyah; Riska Rindayani; Mukhlis Mukhlis; Miftahul Jannah (Jurnal Pendidikan Islam, 2026)
Adolescent self-disclosure plays an important role in students’ social-emotional development, psychological well-being, and participation in educational environments. Although the Johari Window has been widely applied to enhance interpersonal awareness and communication, limited empirical research has examined its pedagogical value for fostering adolescents’ self-disclosure within Islamic educational settings or its contribution to Islamic educational scholarship. This study investigated the effectiveness of Johari Window-based individual counselling in fostering adolescents’ self-disclosure. Five purposively selected eighth-grade students with low self-disclosure participated in three Johari Window-based individual counselling sessions. Self-disclosure and changes in participants’ Johari Window profiles were assessed using the Adolescent Self-Disclosure Questionnaire (KKDR) and the Adolescent Johari Window Questionnaire (KJWR), with outcomes analyzed using paired-samples t-tests and normalized gain scores. The findings revealed a statistically significant improvement in students’ self-disclosure (p < .05), accompanied by a moderate normalized gain (N-gain = 0.59) and a progressive expansion of participants’ Open Areas, indicating enhanced reciprocal communication, interpersonal trust, and self-awareness. These findings demonstrate that Johari Window-based counselling effectively enhances adolescents’ self-disclosure while contributing to Islamic educational scholarship by positioning the Johari Window as a pedagogical framework that integrates reciprocal communication, interpersonal trust, self-awareness, and character development to support students’ social-emotional learning within Islamic educational contexts.